Drought risk in argentine Pampean region - Scarpati, Olga Eugenia (2011)
This paper analyses the drought risk in argentine Pampean region using statistical results of soil water storage. These are calculated by daily soil water balance whose methodology has been tested using values obtained in situ. The goal of the paper is define a level of drought or minimum level of soil water storage, for the entire region which is, at the same time, the minimum optimum soil water content for crops. Over this moisture level, crops can yield with all their potential. The occurrence probability of values, for a determined time period, under that minimum is proposed. The established level of drought is considered as the half of the available soil water capacity, which coincides with the minimum limit of optimum soil moisture (so called conditional drought level). The possibility of the use of crop and/or soil management coefficients, allowing a more particular evaluation for different agricultural exploitation, is also analyzed. The less risk is founded at the corn area par excellence.